Sokolsky’s activity of gymnastic societies on fencing development in territory of Ukraine - Дьоміна, О.; Бусол, В. (Slobozhanskyi Herald of Science and Sport, 2011)
In this article, the chronology of creation of «Sokil» societies is represented and their sport fencing development activity in Ukraine is examined. The role of the sport pedagogues and personalities of «Sokil» development in the formation of organizational, methodical and practical aspects of fencing development basis is exposed. Effectiveness of activity of «Sokil» societies in combining of mass sport activities with cultural and patriotic education of youth.